Mortality and Its Associated Factors among Hospitalized Heart Failure Patients : The Case of South West Ethiopia - Meiraf Daniel Meshesha; Robel Hussen Kabthymer; Mohammed Mecha Abafogi (Cardiology Research and Practice)
Background. Hospital case fatality among those with heart failure in Africa ranges from 9% to 12.5%. An integrated approach to identify those who are at high risk and implementing specific treatment strategies is of great importance for a better outcome. Objective. The aim of this study is to assess the mortality rate and its associated factors among hospitalized heart failure patients at the Jimma University Medical Center (JUMC), south west Ethiopia. Method. A hospital-based retrospective cross-sectional study design was conducted among 252 patients admitted with heart failure during the study period who were sampled and enrolled in to the study. A simple random sampling technique was used to select the study participants by using their medical registration number as the sampling frame. Data were collected using a pretested questionnaire. The collected data were entered into EpiData software and exported to SPSS version 20 for cleaning and analysis. A binary logistic regression model was used. Adjusted and crude odds ratio with 95% CI were used. A P value less than 0.05 was used to declare statistical significance. Results. The prevalence of in-hospital mortality was found to be 21.29%. Cardiogenic shock AOR: 0.016 (95% CI: 0.001–0.267), complication at admission AOR: 5.25 (95% CI: 1.28–21.6), and ejection fraction (<30) AOR: 0.112 (95% CI: 0.022–0.562) were found to be significantly associated factors. Conclusion. The in-hospital mortality rate among admitted heart failure patients is unacceptably high. Due emphasis should be given on the identified associated factors to reduce the mortality.